Front Cover: Host‐Guest Complexes of Dodeka(ethylene)octamine: Prediction of Ion Selectivity by Quantum Chemical Calculations IX (Z. Anorg. Allg. Chem. 10/2019). Issue 10 (17th May 2019) - Puchta, Ralph; Walther, Daniel; März, Matthias; Begel, Svetlana; van Eldik, Rudi
Abstract : In supramolecular chemistry, a metal ion in a box as in Bühl's cryptand, should not move freely. The cation requires good interactions with the donor atoms and a complementary size. This was illustrated by Ms. Angelina Hans, graduate of the art class, Lothar‐von‐Faber‐Schule, Staatliche Fachoberschule, Nürnberg. More details are discussed in the article by Ralph Puchta, Daniel Walther, Matthias März, Svetlana Begel, and Rudi van Eldik on page701 .